2010
DOI: 10.1007/s11664-010-1086-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Multicarrier Transport in LPE-Grown Hg1−x Cd x Te Layers

Abstract: A detailed study is presented of multicarrier transport properties in liquidphase epitaxy (LPE)-grown n-type HgCdTe films using advanced mobility spectrum analysis techniques over the temperature range from 95 K to 300 K. Three separate electron species were identified that contribute to the total conduction, and the temperature-dependent characteristics of carrier concentration and mobility were extracted for each individual carrier species. Detailed analysis allows the three observed contributions to be assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In principle, the carrier type cannot be discriminated from MR measurements since the Hall voltage is effectively zero, however the gate biasing conditions employed guarantee that only electrons contribute to the channel conductivity. The mobility spectrum can be deconvolved from the magnetic field dependent longitudinal conductivity tensor component employing mobility spectrum analysis approaches [8][9][10][11][12]15]. In this study, high-resolution mobility spectrum analysis (HR-MSA) was employed to extract the mobility spectra from the measured magnetic-field dependent magneto-resistance characteristics [11,12].…”
Section: Sample and Analysis Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, the carrier type cannot be discriminated from MR measurements since the Hall voltage is effectively zero, however the gate biasing conditions employed guarantee that only electrons contribute to the channel conductivity. The mobility spectrum can be deconvolved from the magnetic field dependent longitudinal conductivity tensor component employing mobility spectrum analysis approaches [8][9][10][11][12]15]. In this study, high-resolution mobility spectrum analysis (HR-MSA) was employed to extract the mobility spectra from the measured magnetic-field dependent magneto-resistance characteristics [11,12].…”
Section: Sample and Analysis Detailsmentioning
confidence: 99%
“…While this complexity can be somewhat circumvented employing magnetic-field dependent magnetotransport measurements analyzed using multicarrier fitting procedures [7], such data fitting procedures include arbitrary elements that are not adequate for the study of electronic transport in modern semiconductor structures. A more general approach is to employ mobility spectrum analysis to separate and resolve the conductivity-mobility spectra of all carriers present in a sample [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, 2DEG transport in Al 0.3 Ga 0.7 N/AlN/GaN heterostructures have been characterized employing a recently developed high-resolution quantitative mobility spectrum analysis algorithm (HR-QMSA) [12]. It is shown that transport in the channel is due to a single well-defined 2D electron species that exhibits an approximately Gaussian mobility distribution and thermal broadening with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The electron and hole mobility spectra are numerically extracted from the measured conductivity tensor components using numerical inverse mobility transforms, better known as quantitative mobility spectrum analysis algorithms. [7][8][9][10][11][12][13] In this work, the analysis was performed using a recently developed highresolution mobility spectrum analysis algorithm 13 employing a grid of 50 points/decade in mobility. For all temperatures, the measured Hall coefficient was found to be negative and effectively independent of magnetic-field intensity for B Ն 1 T, exhibiting an anisotropy ratio R H,͑Ќ͒ / R H,͑ʈ͒ = 0.976Ϯ 0.001 for T Յ 150 K, while exhibiting marginally more isotropic behavior at room temperature ͑R H,͑Ќ͒ / R H,͑ʈ͒ = 0.984Ϯ 0.002͒.…”
mentioning
confidence: 99%